How Students and Families Use Rankings for College Selection - Ehrenberg, Ronald G.; Walpole, MaryBeth (My University, 2003)
Top-selling college rankings issues published annually by U.S. News & World Report, Business Week, and Money are becoming an increasingly important factor in the competition among institutions of higher education. This forum will discuss how the enormous importance of rankings can tempt universities to alter admissions systems and how these practices, intended to yield a better ranking, may not be in the best interest of students or the institutional mission. Also up for discussion will be how students and parents use the rankings and the publisher's perspective on rankings.
Keywords: University Relations; Leadership and Governance